2286. Revisiting Immune Interference: Evaluation of Immune Response to Yellow Fever Vaccine at Various Time Points Following Live-Attenuated Influenza Vaccination. (26th November 2018) - Blyth, Dana M; Liang, Zhaodong; Williams, Maya; Murray, Clinton K
Abstract: Background: Due to concerns for immune interference, current recommendations are to avoid other live virus vaccines for 30 days pre- and post-mass vaccination campaigns leading to interruptions in routine vaccinations. During rapid preparations for Operation United Assistance (OUA) which supplied humanitarian assistance during the Ebola epidemic, mass yellow fever vaccine (YFV) administration to deploying personnel was needed during ongoing live-attenuated influenza vaccine (LAIV) administration. This study is the first to compare seroconversion rates for YFV when given per guidelines (VBG) to rates when YFV is given 1–29 days post-LAIV (NVBG). Methods: All personnel who received LAIV concurrently or before YFV for OUA and had pre- and post-vaccination archived serum at the Department of Defense Serum Repository were included. VBG was defined as YFV given concurrently or ≥30 days after LAIV and NVBG as YFV given 1–29 days post-LAIV. YFV seroresponse was determined by screening ELISA followed by confirmation with plaque reduction neutralization testing (PRNT) on all positive samples. YFV PRNT ≥1:20 was considered positive. Exclusion criteria were prior YFV and pre-vaccination positive PRNT. Statistical analysis was performed using SPSS v22. Results: During OUA preparations, 676 personnel were vaccinated with LAIV concurrently or before YFV. Sixteen were excluded due to positive pre-vaccination PRNT. Of the 660 who met inclusion criteria, 507 were VBG (482 concurrently and 25 vaccinated ≥30 days post-LAIV) and 153 were NVBG. Median age was 25 (IQR 22, 29) for both groups. Pre-vaccination serum was drawn 280 and 345 days for VBG and NVBG respectively ( P = 0.05). Post-YFV serum was drawn a median of 154 days following YFV in both groups. Seroconversion rates were 98% for VBG and 95% for NVBG ( P = 0.15). Median yellow fever titers were 320 (IQR 160, 640) in both groups post-vaccination. Seroconversion rates were 98% for those with LAIV and YFV concurrently ( n = 471), 100%, 95%, 92%, 100%, and 100% for those with YFV on days 1–6 ( n = 18), days 7–13 ( n = 42), days 14–21 ( n = 66), days 22–27 ( n = 8), and ≥28 days ( n = 44) post-LAIV respectively ( P = 0.12). Conclusion: In this healthy, adult population, YFV provided high levels of protection regardless of timing following LAIV. Disclosures: All authors: No reported disclosures.